A comparative assessment of replication stress markers in the context of telomerase - Eberhart Meessen, Sabine; Najjar, Gregoire; Azoitei, Anca; Iben, Sebastian; Bolenz, Christian; Günes, Cagatay (Cancers, 2022)
Aberrant replication stress (RS) is a source of genome instability and has serious implications for cell survival and tumourigenesis. Therefore, the detection of RS and the identification of the underlying molecular mechanisms are crucial for the understanding of tumourigenesis. Currently, three protein markers—p33-phosphorylated replication protein A2 (pRPA2), γ-phosphorylated H2AX (γ-H2AX), and Tumor Protein P53 Binding Protein 1 (53BP1)—are frequently used to detect RS. However, to our knowledge, there is no report that compares their suitability for the detection of different sources of RS. Therefore, in this study, we evaluate the suitability of pRPA2, γ-H2AX, and 53BP1 for the detection of RS caused by different sources of RS. In addition, we examine their suitability as markers of the telomerase-mediated alleviation of RS. For these purposes, we use here telomerase-negative human fibroblasts (BJ) and their telomerase-immortalized counterparts (BJ-hTERT). Replication stress was induced by the ectopic expression of the oncogenic RAS mutant RASG12V (OI-RS), by the knockdown of ploidy-control genes ORP3 or MAD2 (AI-RS), and by treatment with hydrogen peroxide (ROS-induced RS). The level of RS was determined by immunofluorescence staining for pRPA2, γ-H2AX, and 53BP1. Evaluation of the staining results revealed that pRPA2- and γ-H2AX provide a significant and reliable assessment of OI-RS and AI-RS compared to 53BP1. On the other hand, 53BP1 and pRPA2 proved to be superior to γ-H2AX for the evaluation of ROS-induced RS. Moreover, the data showed that among the tested markers, pRPA2 is best suited to evaluate the telomerase-mediated suppression of all three types of RS. In summary, the data indicate that the choice of marker is important for the evaluation of RS activated through different conditions.
Dieser Artikel gehört zum Special issue: The dual roles of telomeres and telomerase in aging and cancer
Gesehen am 27.02.2024